SOSIALISASI PEMANFAATAN ZOOM MEETING BAGI PENGAJAR TPQ DARUL HIKMAH - Rd. Bily Parancika; Fauzi Isnaen; Fauzan Akbar Albastiah; Warsono Warsono (Journal of Community Service and Engagement, 2022)
The current COVID-19 pandemic has made face-to-face learning into online learning. The students, teachers and administrators must conduct online learning and teaching using online media facilities. The online media used for learning uses zoom because it is more familiar and has many users, so socialization is needed for the use of zoom. The online learning that has been carried out at this time has made student learning possible, and is not constrained by the use of media to carry out learning. However, at this time the teachers and students of TPQ Darul Hikmah who carry out learning and teaching, it is necessary to use Zoom Meetings to interact so that learning can be carried out effectively. The problem so far is that teachers and students only use communication media with Whatsapp, making it difficult for students to absorb the material presented by the teacher because there is no audio and visual interaction and communication via Zoom Meeting. The method of implementing this training activity is carried out online. The output results are the publication of articles in accredited national journals and an increase in the knowledge, skills of TPQ Darul Hikmah teachers and students. Therefore, there needs to be socialization of the use of Zoom Meetings so that teachers can teach students with audio and visuals through Zoom Meetings so that learning can run effectively